Unfolding the Mystery of Life, Biology Lab Manual for Non-Science Majors - Genovesi, Ellen; Blinderman, Laura; Natale, Patrick (Open textbook library., 2019)
This laboratory manual is intended for use in a biology laboratory course taken by non-science majors, pre-biology, and pre-allied health majors. Laboratory exercises provide students with experience in basic laboratory skills, gathering and organizing data, measuring and calculating, hypothesis testing, analysis of data, writing, and laboratory safety. The skill sets are designed to promote the development of critical thought and analysis. Students work with living and preserved specimens, and laboratory reagents and equipment.